Peran Sekolah Terhadap Kesehatan Mental Siswa Sekolah Dasar Selama Pandemi Covid-19 - Susanto, Eri (azkiya, 2023)
Abstract This research was conducted to find out how the role of schools in overcoming students' mental health problems amid the COVID-19 pandemic, especially in primary education. This study uses scientific research methods based on qualitative research with literature studies. This research uses a literature study in Narrative Literature Review (NLR). This research cites research bases in print or online and from accredited scientific journals. The criteria for research sources, both in print and online and from scientific articles, describe mental health problems during the COVID-19 pandemic and have complete sections. The search method for the research base is using the Publish or Perish application which cites a database from Google Scholar using the keywords "Mental health," "the impact of covid-19 in elementary schools", and "The Role of Counseling Teachers during the Pandemic." The research method used is the documentation method, while the analysis of the literature review with four stages is data collection, data shrinkage, data display, and conclusion. The results of this study are that during the pandemic, problems faced by students appeared, including boredom, loneliness, stress, and decreased academic grades. Primary education must have guidance and counseling teachers and counselors who understand student psychology and become the spearhead in overcoming problems due to the pandemic experienced by students. In addition, BK teachers must also have innovations in overcoming the impact of the Covid-19 pandemic experienced by students.